Persepsi Orang Tua Tentang Pola Pengasuhan Anak Terhadap Kemandirian dan Kemampuan Bersosialisasi Anak Usia Dini - Ristianti, Ismi Chanifah; Kisworo, Bagus (Journal of Nonformal Education and Community Empowerment, 2021)
The purpose of this study is to analyze facilitated parenting, early childhood independence, early childhood socializing abilities, and differences in perceptionsabout parenting towards early childhood independence, bringing togetherparenting about the ability to socialize early childhood, questioning concernsabout parenting towards independence and ability socializing early childhood.The study uses a quantitative post-facto method with 35 as samples using quotasampling techniques. The data collection tool used is a questionnaire. The resultsof the study were obtained from the results of the study Concerning parenting onthe independence of early childhood, seen from the results of the F Test with acalculated F score = 9,886> F table = 1,972 and the T-Test showed a T count of2,057 with a sig. Count of 0.042 <0.05. There is a difference in the perception ofparenting towards the ability to socialize early childhood, the results of the F Testwith the calculated F score = 9.886> F table = 1.972 and the T-Test shows Tcount 3.192 with sig. Count 0.002 <0.05. With the competency test with thecalculated F value = 9,886> F table = 1,972 and the T-test shows T count 6,441with sig. Count 0,000 <0,05.